Real World Windows 8 Development - Basu, Samidip. (Apress : Imprint: Apress, 2013)
Real World Windows 8 Development is a developer’s handbook - an essential guide to building complete, end-user ready Windows 8 applications on the XAML and C# programming stack from start to finish. Starting with Windows 8 basics and walking through practical aspects of building your Windows 8 application, you'll find step-by-step instructions and practical advice that will leave you with a modern, elegant app written to the highest of standards.   Author Samidip Basu, an early adopter of Windows 8 app development techniques, breaks down the design, development, and polish of a real-world business application, adding handy tips and tricks around controls, user interface design, storage, navigation, contracts, and more.  Give your Windows 8 application development efforts a kick-start with Real World Windows 8 Development.